A novel bioelectrochemical system for chemical-free permanent treatment of acid mine drainage. (1st December 2017) - Pozo, Guillermo; Pongy, Sebastien; Keller, Jürg; Ledezma, Pablo; Freguia, Stefano
Abstract: The mining sector is currently under unprecedented pressure due to stringent environmental regulations. As a consequence, a permanent acid mine drainage (AMD) treatment is increasingly being regarded as a desirable target with direct benefits for the environment and the operational and economic viability of the resources sector. In this study we demonstrate that a novel bioelectrochemical system (BES) can deliver permanent treatment of acid mine drainage without chemical dosing. The technology consists of a two-cell bioelectrochemical setup to enable the removal of sulfate from the ongoing reduction-oxidation sulfur cycle to less than 550 mg L −1 (85 ± 2% removal from a real AMD of an abandoned silver mine), thereby also reducing salinity at an electrical energy requirement of 10 ± 0.3 kWh kg −1 of SO4 2− -S removed. In addition, the BES operation drove the removal and recovery of the main cations Al, Fe, Mg, Zn at rates of 151 ± 0 g Al m −3 d −1, 179 ± 1 g Fe m −3 d −1, 172 ± 1 g Mg m −3 d −1 and 46 ± 0 g Zn m −3 d −1 into a concentrate stream containing 263 ± 2 mg Al, 279 ± 2 mg Fe, 152 ± 0 mg Mg and 90 ± 0 mg Zn per gram of solid precipitated after BES fed-rate control treatment. The solid metal-sludge was twice less voluminous and 9 times more readily settleable than metal-sludge precipitated using NaOH. The continuous BES treatment also demonstrated the concomitant precipitation of rare earth elements together with yttrium (REY), with up to 498 ± 70 μg Y, 166 ± 27 μg Nd, 155 ± 14 μg Gd per gram of solid, among other high-value metals. The high-REY precipitates could be used to offset the treatment costs. Graphical abstract: Image 1 Highlights: Bioelectrochemical process allows AMD treatment without added chemicals. Elemental sulfur was recovered on graphite granules for up-stream reuse. A less voluminous and more readily metal-sludge is produced during BES treatment. Rare earth elements and yttrium were recovered after BES treatment.